2003
DOI: 10.1007/s00213-003-1562-3
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter polymorphism, 5HTTLPR, is associated with a faster response time to sertraline in an elderly population with major depressive disorder

Abstract: These results suggest that genetic variation in the serotonin transporter gene effects the response time to sertraline and provides complementing evidence to previous reports that this polymorphism affects response time to other SSRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 18 publications
(21 reference statements)
5
70
1
2
Order By: Relevance
“…162 The short/long genotype was recently found to be associated with an odds ratio (OR) of 2.37 concerning adverse effects during treatment with SSRIs (dermatologic reactions, weight change and fatigue above all), and the homozygous short genotype showed an OR of 1.77. 163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes.…”
Section: Comtmentioning
confidence: 73%
“…162 The short/long genotype was recently found to be associated with an odds ratio (OR) of 2.37 concerning adverse effects during treatment with SSRIs (dermatologic reactions, weight change and fatigue above all), and the homozygous short genotype showed an OR of 1.77. 163 These findings are generally well replicated in studies involving white popu lations, 120,[164][165][166][167][168][169][170][171][172][173][174][175] although opposite or inconsistent findings have also been reported. [176][177][178][179][180] On the other hand, studies involving Asian populations usually report conflicting results: some studies reported that the short 5-HTTLPR allele was associated with better outcomes, [181][182][183][184] some found no effect of 5-HTTLPR genotype on treatment efficacy 121,185,186 and some reported that the long 5-HTTLPR allele was associated with better outcomes.…”
Section: Comtmentioning
confidence: 73%
“…The l-allele of the 5-HTTLPR polymorphism is associated with better SSRI antidepressive effects than the s-allele 49,52,53 and with faster response to several SSRI's. 54,55 Combined treatment with a 5-HT 1A blocker to prevent negative feedback at the somatodendritic level compensated for the worse antidepressant effect of SSRIs in s/s and s/l genotypes, 56 suggesting higher 5-HT 1A negative feedback in s-allele genotypes.…”
Section: -Ht Transportermentioning
confidence: 99%
“…84,85 We may not rule out the possibility that gene variants may be indirectly associated with rapid onset through a mechanism of action independent from drugs, for example, predisposing to shorter episodes. This would then imply that gene variants are also associated with placebo response.…”
Section: Assessment Issuesmentioning
confidence: 99%